2015
DOI: 10.3390/catal5020759
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Phosphine Doping and the Surface Metal State of Ni on the Catalytic Performance of Ni/Al2O3 Catalyst

Abstract: Ni-based catalysts as replacement for noble metal catalysts are of particular interest in the catalytic conversion of biomass due to their cheap and satisfactory catalytic activity. The Ni/SiO2 catalyst has been studied for the hydrogenolysis of glycerol, and doping with phosphorus (P) found to improve the catalytic performance significantly because of the formation of Ni2P alloys. However, in the present work we disclose a different catalytic phenomenon for the P-doped Ni/Al2O3 catalyst. We found that doping … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 35 publications
3
18
0
1
Order By: Relevance
“…reported that the conversion of isosorbide and mono‐oxygenated intermediates was identified as the slowest reaction step . Moreover, the production of C 5 species might be because of the decarboxylation or decarbonylation of oxygenate groups at the ends of the carbon chains …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…reported that the conversion of isosorbide and mono‐oxygenated intermediates was identified as the slowest reaction step . Moreover, the production of C 5 species might be because of the decarboxylation or decarbonylation of oxygenate groups at the ends of the carbon chains …”
Section: Resultsmentioning
confidence: 99%
“…Among the alkane products, the selectivity for C 5 /C 6 alkane was approximately 50 %, which is lower than that of the Ru/C+H 3 PO 4 catalytic system. Interestingly, the long‐chain alkane selectivity increased gradually with an increase of the reaction temperature (Figure S8) and reached 74.8 % at 573 K, which could be because of the decomposition of phosphate additives at high reaction temperatures . Moreover, HDO experiments over Ru/C with mineral acids were performed to investigate the role of phosphoric acid.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They explain that electron transfer between active Ru species and SnOx additives modifies the adsorption of the nitro group of the substrate, influencing the product selectivity, and also improves the stability of the catalysts. Li et al [7] report the catalytic performance of phosphorus-doped Ni/Al2O3 catalysts for the hydrogenolysis of a biomass-derived compound of glycerol. These are recyclable and selective catalysts for the production of 1, 2-propanediol.…”
mentioning
confidence: 99%
“…Many group [10] indicate that the addition of phosphorus promotes solubility of molybdate due to the formation of complexes phosphomolybdate, which simulates the preparation of the catalyst. García-Vila et al [11] and Li et al [12] indicated that the addition of phosphorus improves the surface Al 2 O 3 which consumes OH groups of Al 2 O 3 .…”
Section: Introductionmentioning
confidence: 99%